Network Performance Analysis Based on Network Simulator NS-2. - Y. Anad Alsaleem, Maan; Y. Anad Alsaleem, Naors; Ali Zakar, Nawfal (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
NS-2 is a tool to simulate networks and events that occur per packet sequentially based on time and are widely used in the research field. NS-2 comes with NAM (Network Animator) that produces a visual representation it also supports several simulation protocols. The network can be tested end-to-end. This test includes data transmission, delay, jitter, packet-loss ratio and throughput. The Performance Analysis simulates a virtual network and tests for transport layer protocols at the same time with variable data and analyzes simulation results based on the network simulator NS-2.